Outcomes after Multiligament Knee Injury Reconstruction using Novel Graft Constructs and Techniques - Lee, John Hee-Young; Cook, James L.; Wilson, Nichole; Rucinski, Kylee; Stannard, James P. (The Journal of Knee Surgery, 2020)
Clinical outcomes after reconstruction for multiligamentous knee injury (MLKI) can be consistently favorable. However, recent implants and technique advances may allow for improvement in outcomes. Our institution has developed novel graft constructs and techniques for reconstructions with preclinical data supporting clinical use. Our study purpose was to assess clinical outcomes after reconstruction for MKLI using our constructs and techniques. Overall success rate, failure/revision rates, return to work (RTW)/return to sports (RTS) rates, and complications were evaluated testing the hypothesis that novel methods would be associated with clinical benefits with respect to applications and outcomes compared with historical results. We reviewed a single-surgeon, longitudinal database of 42 patients who underwent multiligament reconstruction at our institution using these techniques for at least two-ligament injuries. Visual analogue scale (VAS) pain score and PROMIS (patient-reported outcomes measurement information system) were collected preoperatively and postoperatively at a minimum 1-year follow-up. Among these patients, 33 patients (mean age of 28.9 years, mean body mass index (BMI) of 33.2 kg/m2, mean follow-up of 14.2 months) were included for outcomes analyses. With the definition of success as having a VAS score of less than or equal to 2 without revision/salvage surgery due to recurrent/residual instability or arthritis, overall success rate was 88% (29/33). The mean VAS scores improved from 5 ± 2 to 2 ± 2. The mean preoperative PROMIS mental health score was 36.2 ± 7, general health was 33.5 ± 6, pain was 62.7 ± 8, and physical function score was 29.4 ± 3. At the final follow-up, PROMIS MH was 50.2 ± 10, GH was 44.4 ± 9, pain was 54.3 ± 9, and PF was 42.6 ± 8.4. Return to work rate was 94% (31/33), and 52% (17/33) of patients were able to RTS at any level. Our results demonstrated excellent clinical outcomes associated with a primary success rate of 88% and RTW rate of 94%. Intraoperative complications occurred in 9.5% of cases and revision and failure rates were 9% and 3%, respectively. Our initial results suggest that multiligament reconstructions using novel graft constructs and techniques are safe and effective and can be considered an appropriate option for reconstruction of the full clinical spectrum of MLKIs.
Keywords: multiligament knee injury; multiligament reconstruction; anterior cruciate ligament; posterior cruciate ligament; posterolateral corner